Penerapan Model Pembelajaran SAVI dalam Pembelajaran Bangun Ruang untuk Mengukur Hasil Belajar Matematika - Putri Septia; Viktor Pandra; Novianti Mandasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the mastery of learning outcomes after applying the SAVI learning model (Somatic, Auditory, Visualization, Intellectually) in learning Mathematics for fifth grade students at SDN 13 Lubuklinggau. The research method uses quasi-experiments. The population in this study were all 22 students of class V at SDN 13 Lubuklinggau. Sampling was carried out by means of saturated sampling technique, totaling 22 students as the number of samples. Data collection techniques using tests in the form of essay questions. The data obtained were analyzed using the z-test. Based on the results of research and discussion obtained an average value of 76.29 with learning completeness (81.81%). The results of the z-test analysis obtained Zcount = 2.27 and Ztable = 1.64 which indicates that the hypothesis Ho is rejected and Ha is accepted. So it can be concluded that the mathematics learning outcomes of fifth grade students at SD Negeri 13 Lubuklinggau after the application of the SAVI (Somatic, Auditory, Visualization, Intellectually) learning model is significantly complete. Keywords: SAVI, Learning Outcomes, Mathematics